The teachers' Attitudes toward Mnemonic strategies in improving the basic multiplication facts retrieval among Inclusive Primary School students - Kawai, Norimune; Wulandary, Verra (Jurnal Pendidikan Bitara UPSI, 2025)
The current quasi-experimental comparative study investigated the teachers' attitudes toward Mnemonic strategies (Visual Imagery and Story-linking) compared to Traditional Strategies (Rote Learning, Multiplication Quizzes, Daily Multiplication Habit, and Repeated Addition Strategy) in enhancing basic multiplication fact retrieval among Grade 3 students with and without disabilities in 20 inclusive primary schools. A sequential explanatory mixed-methods design was adopted, prioritizing quantitative analysis to establish causal relationships, followed by qualitative exploration for more profound insight. The Non-equivalent Control Group Design (NECGD) was utilized in the quantitative phase, comprising 20 teachers: 10 in the experimental group (Mnemonic strategies) and 10 in the control group (Traditional Strategies). In addition, the authors administered a pre-test and post-test survey, which included questionnaires and open-ended questions, to measure changes in teachers' attitudes before and after the intervention. Moreover, interviews were conducted with the teachers to gather more in-depth qualitative data. Additionally, a Paired-Samples T-test revealed a statistically significant increase in teachers’ positive attitudes toward Mnemonic strategies following a one-day professional development program (t(9) = 15.00, p < 0.001), indicating that exposure to innovative teaching strategies positively influenced the teachers’ attitudes. Although the control group (Traditional Strategies) also showed significant improvement in their attitudes (t (9) = 9.80, p < 0.001), the experimental group demonstrated a more substantial change, suggesting that Mnemonic strategies were more effective in fostering a positive shift in teacher attitudes. The qualitative findings have also supported the quantitative results, highlighting the increasing confidence of teachers in using Mnemonic strategies to assist students with diverse learning needs. These results contribute to the broader discourse on teacher cognition, instructional efficacy, and inclusive pedagogy, underscoring the necessity of sustained professional development programs in promoting adaptive instructional practices.